Travel time prediction using machine learning and weather impact on traffic conditions - Deb, Bilash; Khan, Salehin Rahman; Khan, Ashikul Haque; Hasan, Khandker Tanvir (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.